Ani Food Legacy / Nurul Anis Qistina Nordin ... [et al.] - Nordin, Nurul Anis Qistina; Mohd Akil, Nur Hidayah; Mohd Hidzir, Aimi Suhaili; Mohd Norri, Nur Sulaiha; Rosli, Nurul Natasya (2021)
Ani Food Legacy was founded and established in 2000 by Norani bt. Md Nor. Located at Sekinchan, Selangor. Initially, she only opened a small stall selling dodol and wajik by the roadside, and by that time, Ani Food Legacy was known as Dodol Ani. The magnificent and uniqueness of Ani Food Legacy is still there to this day and the company still maintains the same delicious taste even though they are using a modern machine instead of using the traditional machine. They are using this modern machine because this company received a lot of demand from the customers. It has been important to the founder, Norani, and her son, Shahrin Azhar b. Rasidi took over the family business to ensure that they maintain the authenticity and taste of both their products. Not just that, in 2016, a myriad of dodol flavors were made available by Ani Food Legacy to make sure the customer taste it differently and found it special because variety is better so that even now it will be better than any other place than Dodol Ani.